Palliative care nursing caring for suffering patients - Perrin, Kathleen Ouimet (Jones & Bartlett Learning, 2012)
Palliative Care Nursing: Caring for Suffering Patients explores the concept of suffering as it relates to nursing practice. This text helps nurses define and recognize various aspects of suffering across the lifespan and within various patient populations while providing guidance in alleviating suffering. Further, Palliative Care Nursing discusses ways nurses as witnesses to suffering can optimize their own coping skills and facilitate personal growth. The text describes nursing interventions to assist those who are suffering, explores spiritual and ethical perspectives on suffering, outlines grief models and how to communicate with individuals who are grieving or suffering, and explores how witnessing suffering impacts nurses' ability to assume the professional role.